2011
DOI: 10.1002/aic.12622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water vapor on gas permeation and separation properties of MFI zeolite membranes at high temperatures

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Understanding the effects of water vapor on gas permeation and separation properties of MFI zeolite membranes, especially at high temperatures, is important to the applications of these zeolite membranes for chemical reactions and separation involving water vapor. The effects of water vapor on H 2 and CO 2 permeation and separation properties of ZSM-5 (Si/Al $ 80) zeolite and aluminum-free silicalite membranes were studied by comparing permeation properties of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…They showed that the inter-crystalline regions can effectively be eliminated using a proper synthesis temperature profile that leads to higher selectivities. However, due to application on unseeded supports, their selectivity ( 22) for the same separation conditions was almost 6 times lower than that of Li et al ( 130). Considering all the above-mentioned facts, to further improve the selectivity of tubular ZSM-5 zeolite membranes, we need to minimize inter-crystalline gaps of the membrane layer via modifying the seeding method and combine it with an appropriate synthesis temperature/time profile.…”
Section: Introductioncontrasting
confidence: 55%
See 2 more Smart Citations
“…They showed that the inter-crystalline regions can effectively be eliminated using a proper synthesis temperature profile that leads to higher selectivities. However, due to application on unseeded supports, their selectivity ( 22) for the same separation conditions was almost 6 times lower than that of Li et al ( 130). Considering all the above-mentioned facts, to further improve the selectivity of tubular ZSM-5 zeolite membranes, we need to minimize inter-crystalline gaps of the membrane layer via modifying the seeding method and combine it with an appropriate synthesis temperature/time profile.…”
Section: Introductioncontrasting
confidence: 55%
“…It can be found from Fig. 9 that the Si/Al ratio of the membrane surface reached 50, reflecting that despite the low Si/Al ratio of initial synthesis solution ( 160) a part of the alumina from the support (as aluminate ions) dissolves in the synthesis solution and is incorporated into the framework of zeolite layer during the secondary growth method [22]. Nevertheless, as it is well known that the hydrophilicity of a zeolite membrane strongly depends on the Si/Al ratio of zeolite layer, the ZSM-5 membranes prepared in this work still could be used for organic/water separation process by pervaporation technique.…”
Section: Effect Of Variable-temperature/time Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Tang et al suggested that gas permeation through modified MFI zeolite membrane could be inhibited by the counter‐diffusion of sweep gas from the opposite side of the membrane. As a small and strong absorbing molecule, H 2 O was thought to bond on SiOH groups which existed in MFI zeolite channel surfaces at LT . However, when the temperature was high enough (especially above 300ºC) that the absorbing capacity of H 2 O in zeolite channels decreased and even disappeared, H 2 O would appear a strong temperature‐sensitive activated diffusion due to its high permeation diffusivity and low activated diffusion energy as related to its small diameter size (0.28 nm) and light molecule mass .…”
Section: Resultsmentioning
confidence: 99%
“…However, the pore size (around 0.55 nm) is relatively large for selective separation of H 2 , resulting in high permeance but low selectivity [29][30][31][32]. To reduce the pore size of MFI-type zeolite, a silane modification strategy was developed by Masuda et al [33] The precursor molecules of silane were introduced into the zeolitic pores and chemisorbed on the active sites (acid sites and metal cations).…”
Section: Introductionmentioning
confidence: 99%